HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN MOTIVASI IBU HAMIL TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DI PUSKESMAS PUTRI AYU KOTA JAMBI - Ervon Veriza; Slamet Riyadi (Poltekkes Kemenkes Jambi, 2018)
Background: Maintenance of oral and dental health in pregnant women is very important to avoid the occurrence of dentaland oral diseases, especially gingivitis (gum inflammation) it is due to changes in hormone levels of estrogen andprogestron in the body of pregnant women.Methods: This study uses analytical survey method is a research method undertaken to explain or describe a situation ina community or community. The sampling technique is accidental sampling where every object that meet with theresearcher is sampled until the number is fulfilled, the sample of this research is pregnant mother at Purti Ayu HealthCenter Jambi City which amounts to 30 people where the total population of pregnant women is 137 people. The analysisused univariate and bivariate analyzes (chi-square test).Results: The knowledge of pregnant women about the maintenance of oral and dental health were at high criteria 16subjects (53%), moderate criteria 14 subjects(47%) and no low criteria. Attitudes of pregnant women about dental andoral health care were at good criteria 12 subjects (40%), moderate criteria 18 subjects (60%) and no poor attitude criteria.While the motivation of pregnant mother about dental and oral hygiene that have motivation were at high criteria 18subjects (60%), moderate criteria are 12 subjects (40%) and no low criteria. Bivariate analysis using Chi-square testshowed that there were a relationship between knowledge with motivation, with p-value = 0,035 and OR = 4. Furthermore,it is known that there were an attitude relationship with motivation, with p-value = 0,048 and OR = 6,2Conclusion: There were a relationship between knowledge and attitude with motivation.